Answer

Verified

449.4k+ views

Hint: We can find pairs by keeping the value of one variable in a given equation and another variable can easily be calculated as it’s just a two-variable equation. Generally, sequential integers are to be used for our ease of understanding.

Complete step-by-step answer:

Here, we have to form such pairs using integers, be it positive or negative, such that $\dfrac{a}{b}=-3$. We can form these pairs by keeping integers on one variable sequentially or randomly, i.e.,

We can start substituting integral values in one variable, let’s say for b

$\dfrac{a}{b}=-3$

Substituting b = 1 in above equation, we get

\[\begin{align}

&\dfrac{a}{b}=-3 \\

&\dfrac{a}{1}=-3 \\

\end{align}\]

On cross-multiplying above equations, we get

\[a=-3\]

One such pair formed by the values calculated above will be i.e., pair 1: (-3, 1).

Again, substituting sequential or random values for b in the given equation i.e., b = -3, 5, 6, 10, we get

For $b=-3$, we get

\[\begin{align}

&\dfrac{a}{b}=-3 \\

&\dfrac{a}{-3}=-3 \\

\end{align}\]

On cross-multiplying above equations, we get

\[\begin{align}

&a=\left( -3 \right)\times \left( -3 \right) \\

&a=9 \\

\end{align}\]

Thus, pairs formed from similar operations in a given equation, we get pair 2: (9, -3).

Similarly, for$b=5$, we get

\[\begin{align}

&\dfrac{a}{b}=-3 \\

&\dfrac{a}{5}=-3 \\

\end{align}\]

On cross-multiplying above equations, we get

\[a=-15\]

Thus, pairs formed from similar operations in a given equation, we get pair 3: (-15, 5).

Now for \[b=6\], we get

\[\begin{align}

&\dfrac{a}{b}=-3 \\

&\dfrac{a}{6}=-3 \\

\end{align}\]

On cross-multiplying above equations, we get

\[a=-18\]

Thus, pairs formed from similar operations in a given equation, we get pair 4: (-18, 6).

Now for \[b=10\], we get

\[\begin{align}

&\dfrac{a}{b}=-3 \\

&\dfrac{a}{10}=-3 \\

\end{align}\]

On cross-multiplying above equations, we get

\[a=-30\]

Thus, pairs formed from similar operations in a given equation, we get pair 5: (-30, 10).

Hence, pairs formed using given conditionality, we get (-3 ,1); (9, -3); (-15, 5); (-18, 6); (-30, 10).

Note: Student might perform a mistake in the sign conventions while substituting values of either a or b in given equation like, \[\dfrac{6}{-2}=\dfrac{-6}{2}=-3\], hence pairs so formed could change from (6, -2) to (-6, 2), unknowingly.

Complete step-by-step answer:

Here, we have to form such pairs using integers, be it positive or negative, such that $\dfrac{a}{b}=-3$. We can form these pairs by keeping integers on one variable sequentially or randomly, i.e.,

We can start substituting integral values in one variable, let’s say for b

$\dfrac{a}{b}=-3$

Substituting b = 1 in above equation, we get

\[\begin{align}

&\dfrac{a}{b}=-3 \\

&\dfrac{a}{1}=-3 \\

\end{align}\]

On cross-multiplying above equations, we get

\[a=-3\]

One such pair formed by the values calculated above will be i.e., pair 1: (-3, 1).

Again, substituting sequential or random values for b in the given equation i.e., b = -3, 5, 6, 10, we get

For $b=-3$, we get

\[\begin{align}

&\dfrac{a}{b}=-3 \\

&\dfrac{a}{-3}=-3 \\

\end{align}\]

On cross-multiplying above equations, we get

\[\begin{align}

&a=\left( -3 \right)\times \left( -3 \right) \\

&a=9 \\

\end{align}\]

Thus, pairs formed from similar operations in a given equation, we get pair 2: (9, -3).

Similarly, for$b=5$, we get

\[\begin{align}

&\dfrac{a}{b}=-3 \\

&\dfrac{a}{5}=-3 \\

\end{align}\]

On cross-multiplying above equations, we get

\[a=-15\]

Thus, pairs formed from similar operations in a given equation, we get pair 3: (-15, 5).

Now for \[b=6\], we get

\[\begin{align}

&\dfrac{a}{b}=-3 \\

&\dfrac{a}{6}=-3 \\

\end{align}\]

On cross-multiplying above equations, we get

\[a=-18\]

Thus, pairs formed from similar operations in a given equation, we get pair 4: (-18, 6).

Now for \[b=10\], we get

\[\begin{align}

&\dfrac{a}{b}=-3 \\

&\dfrac{a}{10}=-3 \\

\end{align}\]

On cross-multiplying above equations, we get

\[a=-30\]

Thus, pairs formed from similar operations in a given equation, we get pair 5: (-30, 10).

Hence, pairs formed using given conditionality, we get (-3 ,1); (9, -3); (-15, 5); (-18, 6); (-30, 10).

Note: Student might perform a mistake in the sign conventions while substituting values of either a or b in given equation like, \[\dfrac{6}{-2}=\dfrac{-6}{2}=-3\], hence pairs so formed could change from (6, -2) to (-6, 2), unknowingly.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

How many crores make 10 million class 7 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths